Digestive stability and transport ability changes of β-lactoglobulin–catechin complexes by M cell model in vitro - Dai, Yan; Yang, Ruoting; Yan, Yuting; Wu, Yong; Meng, Xuanyi; Yang, Anshu; Wu, Zhihua; Shi, Linbo; Li, Xin; Chen, Hongbing (Frontiers in Nutrition, 2022)
The current research on interaction between catechin and protein has focused on non-covalent crosslinking, however, the mechanism of free radical-induced crosslinking between catechin and β-lactoglobulin (BLG) is not known. In this study, β-lactoglobulin was bond to four different catechins (EC, ECG, EGC and EGCG). The structure change of complex was investigated by circular dichroism spectroscopy, UV-Vis spectroscopy and ANS fluorescence spectroscopy. M cell model was constructed to evaluate the transintestinal epithelial transport capacity of complex digestive products. The results showed that catechins are covalently bound to β-lactoglobulin by C-S and C-N bonds and their binding content was EGCG>EGC>ECG>EC. Moreover, catechin could change the secondary structure of β-lactoglobulin, with the decreased α-helix and reduction of the irregular coilings, which lead to the loose spatial structure of the protein. Moreover, the catechin could enhance further the digestibility of β-lactoglobulin. Transport capacity of digestive products of M cell model was about twice of that of the Caco-2 cell model, indicating that M cell model had better antigen transport capacity. The difference between groups indicated that the transport efficiency of digestive products was decreased in the presence of catechin, in which BLG-EGCG and BLG-EGC groups were transported more than those strong of BLG-EC and BLG-ECG groups. The transport efficiency of BLG-catechin complexes were lower than that of BLG, indicating that catechin had play the protective and repair roles on intestinal barrier permeability.